Application of WEQ model in some valleys of the western plateau, Iraq - Mazen Abdullah, Wafaa; Atti, Sabah A (Al-Adab Journal, 2021)
The current study aims to estimate the annual rate of wind erosion using WEQ equation according to climatic data. A model for computing wind erosion was applied on three selected basins extended on 11710 square kilometers in the study area. The results of applied WEQ model identified that, the first basin belong to a severe erosion conditions, whereas, the second basin was under moderate erosion condition, while, the third basin come within a weak erosion condition. The study concluded that, the wind is one of the most important corrosive factors in modification and reforming the landforms and landscapes in the study area as illustrated in forms of wind caves and hills. The wind erosion depends on its ability and activity in ablation and sculpting processes. The wind speed is one of the most important factors affecting the process of erosion in dry areas. The susceptibility of wind to erosion is related directly to the wind speed, as the wind can transport sand particles with diameter not more than 0.2 mm with speed ranges between (4.5 -6.7) m/s.